The Effectiveness of Giving 25% Green Betel Leaf Extract Formula (Piper Betle) in Reducing Germ Numbers on the Emergency Room Floor of RSU "X" Ponorogo Regency - Rohmatin, Santi Lisdiana; Sakufa, Avicena; Widiarini, Retno (Journal of Comprehensive Science, 2024)
Hospitals are places of service that aim to achieve optimal health for the community. In addition to seeking cures, hospitals are also a source of various diseases for both patients and visitors. The disease is caused by pathogenic microorganisms that multiply in the air, water, floor, food, medical and non-medical equipment. One of the most common hospital-acquired infections in the Emergency Department (ER) is nosocomial infection. The purpose of this study is to determine the effectiveness of the use of green betel leaf extract (Piper betel) in reducing the number of germs on the emergency room floor at the x Hospital of Ponorogo Regency. The method used in this study is experimental, with the analysis being Quasi-Experimental and using Pretest-posttest Group Design. The percentage of effectiveness in reducing the number of germs in the 25% formula is 86.78%, the 20% formula is 85.40%, the 15%  formula is 8 1.96%, and the 10% formula is 75%. There was a decrease in the number of germs on the floor of the emergency room using green betel leaf extract (Piper Beetle). The effectiveness of green betel leaf extract on the floor swab test is found in the 25% formula. In addition, a long soaking method and a higher formula can be used to measure the effectiveness of green betel leaf extract as an antibacterial in reducing the number of germs on the floor.